PREVALENCE AND SCREENING OF PHIMOSIS IN TODDLERS AT THE INTEGRATED SERVICE POST WITHIN THE WORKING AREA OF WAGIR COMMUNITY HEALTH CENTER, MALANG REGENCY - Clark Rizqullah Suhermanto, Muhammad; Daryanto, Besut; Nurhadi, Pradana (Indonesian Urological Association, 2025)
Objective: This study aimed to determine the prevalence of phimosis in toddlers at the health posts within the working area of the Wagir Health Center, Malang Regency, assess parents' knowledge, and analyze the factors that influenced parents' knowledge about phimosis. Material & Methods: This study was descriptive and observational analytical and involved 248 male toddlers. Data were obtained through questionnaire responses and physical Examination which were then analyzed using the SPSS software by Pearson’s Chi-Square comparative test and Binary Logistic regression. Results: Phimosis cases were found in 71.77% of 248 toddlers, with 82.6% of them having parents with a lack of knowledge. There was a significant association (p-value <0.05) between family history factors and parents' income level with parents' knowledge of phimosis. However, there was no significant relationship (p-value > 0.05) between the factors of parents' education history and the access to healthcare facilities with parents' knowledge of phimosis. Conclusion: Parents' knowledge of phimosis is low or still lacking. Keywords: Phimosis, parents' knowledge, sociodemographic factors, health factors, prevalence.